2018
DOI: 10.1002/jeab.461
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral control by the response–reinforcer correlation

Abstract: Using a discrete-trials procedure, two experiments examined the effects of response-reinforcer correlations on responding while controlling molecular variables that operated at the moment of reinforcer delivery (e.g., response-reinforcer temporal contiguity, interresponse times preceding reinforcement). Each trial consisted of three successive components: Response, Timeout, and Reinforcement, with the duration of each component held constant. The correlation between the number of responses in the Response comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Baum () showed that pigeons readily distinguish positive from negative temporally extended contingencies. Kuroda and Lattal () found that pigeons distinguish extended contingency from noncontingency even when local contingencies are equated.…”
Section: Discussionmentioning
confidence: 99%
“…Baum () showed that pigeons readily distinguish positive from negative temporally extended contingencies. Kuroda and Lattal () found that pigeons distinguish extended contingency from noncontingency even when local contingencies are equated.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular view entails two propositions: (a) behavior consists of discrete responses (an ontological commitment); and (b) reinforcers strengthen responses that they follow closely in time (a theoretical commitment). The theoretical commitment that response–reinforcer contiguity alone increases behavior has been challenged multiple times since the 1960s by research indicating that contiguity is neither necessary nor sufficient (Baum, ; Kuroda & Lattal, ; Rescorla, , , ). The ontological commitment to discrete responses also has been challenged since the 1960s by research and argument indicating that behavior is better understood as consisting of temporally extended activities or patterns of behavior (Baum, , ; Baum & Rachlin, ).…”
mentioning
confidence: 99%
“…With a little imagination, these examples could be construed as broadly response dependent. It could be suggested, for example, that there may have been a molar contingency between responding and the "highly valued reinforcer" (see Kuroda & Lattal, 2018, for an example of the effects of such molar contingencies on responding) when it is delivered at the end of that particularly productive training session. It also could be that the jackpot functions like an accumulation contingency (e.g., DeLeon et al, 2014), whereby the participant earns reinforcers but postpones receipt until the end of the session.…”
mentioning
confidence: 99%